Предмет: Математика,
автор: Shadow007
Упростите выражение 3 - 4/x-1 + 7/x
Приложения:
Ответы
Автор ответа:
0
Решение
3 - 4/(x-1) + 7/x = [3*(x² - x) - 4*x + 7*(x - 1)] / (x² - x) =
= (3x² - 3x - 4x + 7x - 7) / (x² - x) = (3x² - 7) / (x² - x)
3 - 4/(x-1) + 7/x = [3*(x² - x) - 4*x + 7*(x - 1)] / (x² - x) =
= (3x² - 3x - 4x + 7x - 7) / (x² - x) = (3x² - 7) / (x² - x)
Похожие вопросы
Предмет: Математика,
автор: danelyamaus2010
Предмет: Русский язык,
автор: aishaturanova
Предмет: Другие предметы,
автор: pv8093881
Предмет: Химия,
автор: anna1799loginova
Предмет: Математика,
автор: cooldenmax2013